Vaccine hesitancy and implications on childhood immunisation in Malaysia - Abd. Manaf, Noor Hazilah; Omar, Mohd Azahadi; Suib, Fatin Husna (Emerald Publishing Limited, 2021)
Purpose The World Health Organization identified vaccine hesitancy as one of the ten threats to global health in 2019. The purpose of this paper is to evaluate the implications and factors affecting parental decision on childhood immunisation in Malaysia.